Remittances from Tongan migrant workers: Channels, costs, and potential gains from switching - Hiroshi Maeda; Ryan Barclay Edwards; Daniel Suryadarma (Asian Development Bank Institute (ADBI), 2024)
The background of high remittance costs and countermeasures against the issue has drawn the attention of policymakers in the Pacific island countries in maximizing the benefits of migration and remittances on their economic development. We use a newly collected household survey about temporary migration in the region and implement a data audit on remittance costs to examine the current state of the remittance market and household decision-making around remittance channels in Tonga. We find that the household choice of remittance channels leads to a higher remittance cost because a large gap in remittance costs exists between high-cost and low-cost remittance service providers. Tongan workers choose high-cost providers mainly because of their ease of use. Within this context, Tongan households and the economy can gain more than 2% of remittances by switching to the lowest-cost providers. We also find that exposure to new information thanks to migration experiences, frequent remittances, and residential islands are the key household characteristics to voluntarily shift from cash transfers to online transfers or mobile money. The findings indicate that micro-level intervention on the household choice of remittance channels and providers can potentially contribute to reducing remittance costs in the region, but we first need to identify the barrier to switching to low-cost providers to design effective policy interventions.
Keywords: F24; O15; 330; remittance costs; migration; Tonga